Organocatalytic Formal Intramolecular [3+2]‐Cycloaddition to Acquire Biologically Important Methanodibenzo[a, f]azulenes and Methanobenzo[f]azulenes. Issue 62 (15th October 2019) - Peraka, Swamy; Pasha, Mohammed Anif; Thirupathi, Guguloth; Ramachary, Dhevalapally B.
Abstract: Lawsones were transformed into the functionally rich framework of methanodibenzo[ a, f ]azulenes and methanobenzo[ f ]azulenes in a single‐ or two‐pot operation through five organocatalytic sequential reactions in very good yields with excellent selectivities. These resultant molecules are basic skeletons of important antibiotics, which highlights the value of this formal intramolecular [3+2]‐cycloaddition as a key protocol. Abstract : Lawsones were directly transformed into the unique carbon skeleton of methanodibenzo[ a, f ]azulenes and methanobenzo[ f ]azulenes through a single‐ or double‐pot operation by using the organocatalytic formal intramolecular [3+2]‐cycloaddition as the key reaction in very good yields with excellent selectivities.